IMPACT OF TRAINING AND DEVELOPMENT PROGRAM ON PERCEIVED PERFORMANCE OF EMPLOYEES IN BSF, KSA - Kholoud Baleelah; Noshaba Batool (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
While the banking organizations are spending much time, resources, and money to provide training and development program for the employees. This study examines the impact of these programs on perceived performance of employees in the Banque of Saudi Fransi (BSF) through online survey method. This study outlined on the opportunities for BSF workers and how they perceived of the impact of the developmental programs on their performance. The obtained results indicate that training and development programs have a positive impact not only on the organizations and banking sectors but also increases the self-confidence of the employees